School-based relationship and sexuality education: what has changed since the release of the Australian Curriculum?. Issue 6 (1st November 2020) - Ezer, Paulina; Kerr, Lucille; Fisher, Christopher M.; Waling, Andrea; Bellamy, Rosalind; Lucke, Jayne
ABSTRACT: Effective school-based relationship and sexuality education (RSE) can improve youth sexual outcomes, including knowledge and behaviour. National pedagogical guidance in the form of the Australian Curriculum: Health and Physical Education (AC: HPE), which includes RSE, was released in 2015. This study sought to determine the sexual health knowledge and school-based RSE experiences of Australian students since the release of the AC: HPE. It presents findings from the Sixth National Survey of Secondary Students and Adolescent Sexual Health, which surveyed 6, 180 Australian Year 10, 11 and 12 students. Findings are compared to those from the same survey conducted in 2013 – prior to the release of the AC: HPE. Analyses examined the associations between perceived relevance of RSE and demographic characteristics/context of RSE; and between sexual health knowledge, demographic characteristics and receipt of RSE. A thematic analysis of responses to an open-ended question provides additional context. Findings indicate that the AC: HPE has had little impact on RSE experiences and sexual health knowledge as findings remain mostly unchanged from 2013: overall knowledge scores have remained moderate to low and peak among young people aged 16–18 in year 12 at school even though most receive RSE in earlier years. Students value their RSE, but their comments reflect inconsistent teaching.